Combined Effect of Genotype, Housing System, and Calcium on Performance and Eggshell Quality of Laying Hens - Ketta, Mohamed; Tůmová, Eva; Englmaierová, Michaela; Chodová, Darina (Animals, 2020)
The objective of this study was to evaluate hen performance and eggshell quality response to genotype, housing system, and feed calcium (Ca) level. For this purpose, an experiment was conducted on 360 laying hens of ISA Brown, Bovans Brown (commercial hybrids), and Moravia BSL (traditional Czech hybrid). Laying hens were kept in enriched cages and on littered floor and fed similar feed mixtures with different Ca content (3.00% vs. 3.50%). In terms of hen performance, ISA Brown had the highest egg production (84.2%) compared to Moravia BSL (74.3%) and Bovans Brown (71.4%). Regarding eggshell quality, Bovans Brown showed the highest values of all eggshell quality parameters. Increasing feed Ca level augmented egg production (p ≤ 0.001) but had no effect on other performance parameters. Except eggshell thickness, all eggshell quality parameters were affected by the three-way interaction of genotype, housing, and Ca. Bovans Brown, which had the strongest eggshells (5089 g/cm2) when housed on a littered floor system and fed 3.00% Ca, while Moravia BSL housed on a littered floor had the weakest eggshells (4236 g/cm2) at 3.50% Ca. The study pointed out the importance of the interactions between studied factors on performance and eggshell quality compared to an individual factor effect.
Keywords: enriched cages; genotype; Ca; littered floor; eggshell; hen performance